(untitled) (Journal of history, 2025)
The representatives of the «Zar Zaman» movement engaged in an ideological struggle against Russian colonization, reflecting in their works the transformation of the traditional Kazakh way of life, the loss of control over land and water resources, the permissiveness and corruption of the ruling authorities, the transformation of spirituality, moral degradation, and the decline of religious values. This article examines the complete archival version of I. Altynsarin’s published work «The Grief of a Kyrgyz». In this work, Altynsarin sought to demonstrate the failure of the Russian Empire’s administrative reforms. In later studies, this work was classified within the «Zar Zaman» movement. The literary works of «Zar Zaman» encapsulated the public consciousness of the Kazakh people. The objective of this study is to analyze the «Zar Zaman» literary movement as the ideological core of the Kazakh people’s resistance to colonialism, as well as to assess its scholarly interpretations and compare them with the perspectives of its contemporaries. In this context, «Zar Zaman» should be regarded not only as an object of literary analysis but also as a socio-political movement warranting attention from historians. There exist specialized studies on the «Zar Zaman» movement among other peoples subjected to the colonial rule of the Russian Empire, including the kyrgyz and karakalpaks. To achieve the research objectives, interdisciplinary decomposition, selection, hermeneutic, and descriptive methods were employed. This article presents, for the first time, an analysis of the works of «Zar Zaman» poets not only in terms of their glorification of the past but also in relation to their assessment of the future. Particular attention is paid to the fact that the crisis sentiments induced by colonial oppression resonate in the works of other Kazakh intellectuals of the time. This suggests not a contradiction but rather an internal coherence in their perspectives. Scholarly research has traditionally characterized «Zar Zaman» as a literary movement marked by nostalgia for the past, disillusionment, and prophetic motifs. However, this study demonstrates that these works provided an unembellished representation of contemporary realities, avoiding idealization or artistic distortion. The texts vividly depict the Kazakh way of life, their internal state, and their perception of external pressures. Furthermore, the article explores the consequences of colonial policies, particularly the dichotomy between resistance and submission, as well as the historical factors that contributed to the formation of a dependent society.